COPING STRESS ON MOTHERS OF AUTISTIC CHILD - Rahmita, Hirza; Pratiwi, Cesa Septiana (International Journal of Psychosocial Rehabilitation, 2020)
The previous research mentioned that mother with autistic child has higher stress level compared to mother with normal child development. Stress that is not handled well can cause impact on the mother who has autistic child. This scoping review used Arksey and O’Malley framerowk which consisted of 5 stages such as identifying research question, identifying relevant articles, selecting the articles, making data chart and arrange them, summarizing and reporting the research result. Using web confidence application for selecting 111 relevant articles until 11 articles left to be reviewed. The review results mapped some themes such as coping form, initial response, and factor which influence coping stress on mother with autistic child. Literature gap found was that coping stress of mother with autistic child is not mostly done yet in developed countries with low income. Mixed method design was rarely used to investigate coping stress and guideline and special service for coping with stress on mother with autistic child are not available yet.